Breaking the Sound Barrier: Deafness and Music in CODA and Other Movies. (3rd July 2022) - Beck, Bernard
Abstract : CODA is an honored movie that combines important elements of several recent movies. The presentations of a thriving deaf community and a unique artistic community are rich and nuanced. The dilemma of a world dependent on high quality sound and a world without sound are explored and made poignant. The complexities of lives managed between separate and seemingly incompatible cultures are revealed in human perspective.